Vitamin B6–Responsive Epilepsy due to a Novel KCNQ2 Mutation - Klotz, Kerstin Alexandra; Lemke, Johannes R.; Korinthenberg, Rudolf; Jacobs, Julia (Neuropediatrics, 2017)
Mutations in KCNQ2, encoding for subunits of potassium channels, are known to cause neonatal epileptic encephalopathy (NEE). Therapeutic options for these children are often limited. Recently, there are indications that some patients with KCNQ2 NEE show seizure response to vitamin B6 (VB6) therapy. We present a young infant with severe KCNQ2 encephalopathy resulting from a novel de novo mutation (c.1023G>C; p.(Gln341His)). In our patient, VB6 responsiveness could be demonstrated clearly by remarkable seizure-response to VB6 therapy and seizure exacerbation to discontinuation of VB6 therapy. The pathophysiology of VB6 response in potassium channel mutations is not understood. Some hypothetical mechanisms are currently in discussion. To identify the group of patients who benefits from VB6 therapy, further investigations are necessary.
Keywords: KCNQ2; vitamin B6; pyridoxine-responsive-epilepsy; neonatal epileptic encephalopathy